Bridging change and project management: A review and future research directions - Elina Jääskä; Kirsi Aaltonen; Liina Hellens; Jaakko Kujala (Project Leadership and Society)
The fundamental purpose of a project is to implement change, aiming for the transition from an existing state to a desired future state. However, project management studies primarily focus on the design and implementation of the project deliverable and rarely address the management of change needed to achieve the desired future state. This study conducted a systematic literature review to synthesize the existing research on change management within project studies and identify areas of contention and under-researched aspects before proposing an agenda for further research. It addresses the following research question: How is the management of change addressed in project studies? The analysis of prior research reveals six key themes: relationship between change management and project management, change process and factors and factors affecting the change process, change management as a success factor, change resistance, interface with permanent organizations, and change in project-based firms and industries/fields. However, this analysis also highlights the fragmented nature of prior research, emphasizing the need for more conceptual and empirical work to understand the integration of change and project management processes. Integrating change management concepts and tools into project management thinking and vice versa offers opportunities to advance both disciplines.